2007
DOI: 10.4000/lidil.2473
|View full text |Cite
|
Sign up to set email alerts
|

Échanges exolingues et interculturalité dans un environnement informatisé plurilingue

Abstract: Ce document a été généré automatiquement le 1 mai 2019. © Lidil 10 Cadre d'analyse et méthodologie 11 Sur la base des références exposées, nous distinguerons dans notre analyse trois types de manifestations de l'interculturalité : Échanges exolingues et interculturalité dans un environnement informatisé plu..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This could create quality issues with the synthesis if we are not interpreting studies properly due our own linguistic limitations. We acknowledge the valuable research on plurilingual pedagogy in other languages (e.g., Arismendi, 2011;Carinhas et al, 2020;Degache et al, 2007;Garbarino, 2015;Maynard & Armand, 2016;Moore et al, 2020), and that the restriction of the synthesis to papers in English is a limitation of our study which we will return to later.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…This could create quality issues with the synthesis if we are not interpreting studies properly due our own linguistic limitations. We acknowledge the valuable research on plurilingual pedagogy in other languages (e.g., Arismendi, 2011;Carinhas et al, 2020;Degache et al, 2007;Garbarino, 2015;Maynard & Armand, 2016;Moore et al, 2020), and that the restriction of the synthesis to papers in English is a limitation of our study which we will return to later.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…In this regard, our experience of linguistic-intercultural exchange within the EULIC project has shown that "[the] intercultural potential of such a training system generates strong motivation" among learners (Degache et al, 2007).…”
Section: Interculturality: a Generator Of Motivationmentioning
confidence: 99%
“…1 (2007, p. 26) [our translation] However, it is worth highlighting, from an exolingual 2 perspective, such as the one that will constitute our object of study, that some work that has been carried out, focus on the development of PC and IC. Those studies emphasize different electronic communication tools (O'Dowd, 2007), such as discussion forums (Degache, L opez Alonso, & S er e, 2007), chats (Ara ujo e S a & Melo, 2007) and e-mails (Belz, 2007). Until today, studies which have focused on blogs as a pedagogical space of development of such skills have been rare (as stated in Wang & V asquez, 2012's meta-analytical study;Belz & Thorne, 2006;Elola & Oskoz, 2008 provide however excellent examples).…”
Section: Introductionmentioning
confidence: 99%